Organic Waste Treatment Optimization Design Planning Using Simultaneous Composting Technology with EM4 and MOL at Universitas Pembangunan Nasional “Veteran” Jawa Timur - Hidayah, Euis Nurul; Novembrianto , Rizka; Rosariawari, Firra; Nisa, Syadzadhiya Qothrunada Zakiyayasin; Sholikin, Mohamad; Rizki, Azizah Mahirah; Rositasari, Putri Redita (Future Science, 2023)
Universitas Pembangunan Nasional “Veteran” Jawa Timur is one of the public facilities that produces solid waste, including organic waste, inorganic, and hazardous waste. Waste that can be immediately utilized is organic waste consisting of food waste and leaves and twigs. Therefore, appropriate technology is needed to process organic waste into more useful goods and as a better management alternative through community service. One of the alternatives for processing waste is recycling it into compost using Simultaneous Composting Technology with EM4 and MOL. The main target of this community service is to reduce waste and utilize university waste with appropriate technology for regional coverage and national coverage in the future. The method of this community service is to separate waste between organic and non-organic, selected organic waste is cut by a hammer mill, and then other waste from the canteen activity is made Local Microorganisms (MOLs) as the decaying medium in the composite production of the organic garbage processing device reactor. As a result, this community service has been running smoothly and well. The results of this community service have a positive impact through the use of organic waste into compost which can be utilized by the internal campus and generate economic value.